Concepts and Features of Aspect-Oriented Programming Using Aspect.Net Framework: A New Approach to Modularization - Mundra, Sakshi; Bansal, Varsha; Vyas, Vaibhav (International journal of advanced research in computer science, 2013)
Aspect Oriented Programming methodology is based on the idea that computer systems can be programmed very efficiently by specifying the various concerns of a system and some description of their relationships separately and then relying the mechanisms in the underlying AOP environment to weave them together into a coherent program automatically. The term Aspect Oriented Programming includes Multidimensional Separation of Concerns, along with Subject Oriented Programming, Adaptive Programming and Composition Filters. Multidimensional Separation of Concerns (MDSOC) permits the encapsulation of various kinds of concerns simultaneously and the integration of separate concerns. The Aspect.NET Framework is implemented as an add-in to visual studio.NET. Now, the user can use Aspect.NET in combination to the integration development environment provided by Visual Studio.NET and all its various features for the development of software applications using AOP methodology.